OSMANLI İDARESİNDE ŞAM (1750-1800) - SAMIKIRAN, OĞUZHAN (Fırat Üniveristesi, 2013)
516 yılından sonra Şam ve Arap dünyası Osmanlıların egemenliği altına girmiş ve Şam, Ortadoğu?da Osmanlının en önemli eyâleti hâline gelmiştir. Şam, hacc kafilelerinin toplanma merkezi olduktan sonra hızla gelişme kaydetmiştir. Osmanlılar, dinî farizayı yerine getirmek maksadıyla hayata geçirdiği idarî, askerî ve iktisadî kararlar ve girişimler Şam?ın gelişmesine imkân sağlamıştır. XVIII. yüzyılın hemen başlarında Hacc Emîrliği Şam valilerine tevcih edilmiş, böylelikle valilerin imparatorluk seferlerine iştirâki sona ermiştir. Merkezî hükûmetin aldığı bu idarî karar, bölgede hem Osmanlı Devleti hem eyâlet halkı hem de Şam valileri için yeni bir dönemin başlangıcı olmuştur. Coğafyanın ve merkezî hükûmetin Şam?a bahşettiği olanaklar sadece şehrin şekillenmesine katkı sağlamakla kalmamış, aynı zamanda şehirde yaşayan idârî, askerî,iktisâdî, dinî ve toplumsal bütün gruplara güç kazandırmıştır. Gruplarca elde edilmiş olanbu güç ise eyâletteki gruplar arasında rekabetin kaynağını teşkil etmiştir.Anahtar Kelimeler: Osmanlı Devleti, Ortadoğu, Şam, Araplar

After 1516, the province of Damascus and the Arab world has entered under the domination of Ottomans and after this date Damascus has been the important province of Ottomans in the Middle East. Damascus had developed speedily, after being the concentration center of hajj coffle. The administrative, military and economic decisions and the attempts which the Ottomans put into practice on account of carrying out thisreligious obligation had provided the development of Damascus. Just in the beginnings of the 18th century, the Emâret of Hajj had been appropriated to the governors of Damascus,by this way the participation to the empire campaigns of Damascus governors had ended.This administrative decision of the central government was the beginning of a new period for both Ottoman State, the people of the province and the governors of Damascus. The possibilities that the geography and central government bestowed upon Damascus not only gavehelpfor the formation of the city, but also had given power to the whole administrative, military, economic, religious and social groups who were living in the city. This power which had been gained by these groups constituted the source of the competition among them in the province.Keywords: Ottoman Empire, The Middle East, Damascus, Arabs
Damascus under the government of Ottoman (1750-1800)
Keywords: Tarih